Observation of the Υ(1 3 D J ) bottomonium state through decays to π + π − Υ(1S) - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
Based on 122×106Υ(3S) events collected with the BABAR detector, we have observed the Υ(13DJ) bottomonium state through the Υ(3S)→γγΥ(13DJ)→γγπ+π−Υ(1S) decay chain. The significance for the J=2 member of the Υ(13DJ) triplet is 5.8 standard deviations including systematic uncertainties. The mass of the J=2 state is determined to be 10 164.5±0.8(stat)±0.5(syst) MeV/c2. We use the π+π− invariant mass distribution to confirm the consistency of the observed state with the orbital angular momentum assignment of the Υ(13DJ).